REPORT OF A STRIPED DOLPHIN, Stenella coeruleoalba (Meyen, 1833) DEATH CAUSED BY GHOST FISHING IN SOUTH WEST COAST OF INDIA - SARLIN, PATHISSERY JOHN; MORRIS, SANCIA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
A male striped dolphin, was found entangled in discarded fishing net, off Tangassery, Coast, Kollam, Kerala, India (8°52′55″N76°34′26″E) by the Coastal Police Patrol to be identified later, as Stenella coeruleoalba. The trapped animal was in a state of fatigue ensued by the struggle to free itself from the ensnaring monofilament driftnet. Necropsy revealed that the stomach was devoid of solid food indicating prolonged starvation caused by the ensnared net. The incident highlights the devastating impact of abandoned fishing gear on our marine wildlife.